Coaches` experience of the importance, development and integration of decision-making and visual exploratory behaviour in an elite football academy setting - Maskell, C.; van Paridon, K. N.; Keyes, H.; Timmis, M. A.; Cavallerio, F. (Sports Coaching Review, 2024)
Effective visual exploratory activity (VEA) and decision-making are integral to being an elite football player. Despite this, there is a lack of understanding regarding how these skills are coached and developed in a youth academy setting. Twelve male, football club youth academy coaches were interviewed to develop an understanding of their approach to coaching VEA and decision-making. Using a reflexive thematic analysis, the findings highlight that in order to maximise the impact of developing VEA and decision-making, coaches and players need to work together to create a shared understanding and common language using a combination of questions, phrases and video analysis. Integrating VEA and decision-making successfully in developmental sessions were viewed as most effective in opposed, chaotic training, which provides frequent opportunity for players to utilise problem solving skills (cf. develop conditional knowledge). Developing and delivering "chaotic" sessions was impacted by coach experience and development of the coach-player relationship.